JEWISH IMMIGRATION AS AN ISSUE IN SOUTH AFRICAN POLITICS, 1937-39 (Historia, 2021)
The Aliens Act, 1937Richard Stuttaford, as Minister of the Interior in the Fusion Cabinet (United Party Government) in 1937, inherited the problem of growing Anti-Semitism which had found sanctuary within the Purified Nationalist Party of Dr D F Malan and had resulted from the influx of Jews from Europe into South Africa in the wake of the repressive racialism of the Nazi Fuehrer, in 1930. Owing to the relatively large immigration from eastern Europe, mainly of Jews, the Quota Bill was piloted through parliament by Dr D F Malan, Minister of the Interior, at the time. The Bill set a limit to the number of immigrants permitted to enter the Union from eastern Europe, but for the rest, the door remained open. Though the Quota Bill did not specifically mention Jews, it could not be denied that it was directed against them, and it was for that reason that Jan Smuts, heading the South African Party, led his reluctant followers in-to opposition against the Bill.
Keywords: Anti-Semitism; History; Jewish immigration; Aliens Act, 1937; Aliens Amendment Bill, 1939; Quota Act; Politics